ANALISIS KEEKONOMIAN PROYEK GAS-TO-LIQUID SEBAGAI ALTERNATIF PEMANFAATAN CADANGAN GAS ALAM INDONESIA - Muhammad Abizar Algiffary Thahir; Dwi Atty Mardiana (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2018)
The reservoir on Field A that has an estimated large reserve of natural gas of 10,73 TSCF would have a potential economic value when developed correctly. The natural gas reserve is planned to be extracted by utilizing 18 subsea production wells connected to five subsea manifolds at a depth of 300 ‒ 1000 m at below sea level. Gas production will be done by using FPSO. Produced gas then will be pumped to onshore processing facilities on Yamdena island through undersea pipeline that used corrosion resistant alloy as long as up to 100 km in length. The natural gas processing would either be done by building an LNG facility scenario or building a GTL facility scenario on Yamdena island. The LNG scenario would produce the natural gas into LNG and gas condensate. While the GTL scenario would produce the natural gas as a synthetic liquid fuel such as LPG, naphtha, kerosene, and diesel. The feed gas volume used on both scenarios is assumed to be 1.041 MMSCFD. The economic indicator calculated for GTL yields an NPV of 1.743,44 MMUS$ and for LNG yields 1.940,51 MMUS$. The IRR calculated for GTL yields 13,27% and for LNG yields 13,14%. The POT period calculated from cummulative cash inflow for GTL scenario will take 9,84 years time, while on LNG scenario POT will take 9,90 years time. The PI value calculated for GTL scenario yields a value of 1,46 and for LNG scenario yields a value of 1,44. Results from sensitivity analyses on economic indicator found that the parameters which has significant effect on the change of economic indicator values are product sell price.